Differentiating follicular thyroid carcinoma from the follicular variant of papillary thyroid carcinoma - Rikhotso, Tshikani Norman (Department of Pathology, 2023)
Introduction: Differentiating follicular adenoma (FA), follicular thyroid carcinoma (FTC) and follicular variant of papillary thyroid carcinoma (FVPTC) remain a diagnostic challenge in some cases. This is as a result of the assessment of nuclear features being highly subjective, and the threshold for confirming cytomorphological features for papillary thyroid carcinoma varying greatly among pathologists which results in poor interobserver agreement. Diagnostic challenges may be encountered with some encapsulated follicular-patterned neoplasms of the thyroid due to uncertainty about the presence of capsular or vascular invasion. Immunohistochemistry may provide a better alternative to distinguishing these entities. Aims and objectives: To study the expression of biomarkers HBME-1, CD15, CK-19 and BRAF V600E in follicular adenoma, follicular carcinoma and follicular variant of papillary thyroid carcinoma. To ascertain the usefulness of these markers in differentiating these follicular-patterned thyroid neoplasms. Materials and methods: This is a ten-year retrospective study in which seventy-nine cases consisting of follicular adenoma (n=26), follicular thyroid carcinoma (n=25) and follicular variant of papillary thyroid carcinoma (n=28) were retrieved and reviewed. Four immunohistochemical stains (CD15, CK-19, HBME-1 and BRAF V600E) were performed and scored in tumour tissue. Data were analysed to determine if there was any correlation between the expression of the immunomarkers and the three follicular patterned thyroid neoplasms. Results: The patients' ages ranged from 13 to 74 years. There was a female bias with a female-to-male ratio of 4:1. HBME-1 expression showing varying intensity and proportion was seen in 7 (28%) FA, 15 (65%) FTC and 22 (79%) FVPTC. CK-19 expression showing varying intensity and proportion was seen in 5 (19%) FA, 3 (13%) FTC and 18 (72%) FVPTC. BRAF V600E expression showing varying intensities and proportions was seen in 3 (11%) of FVPTC. FA and FTC cases were all negative for BRAF V600E. CD15 expression showing varying intensity and proportion was seen in 2 (8%) FA, 6 (24%) FTC and 9 (33%) FVPTC. Statistical analysis detected a significant association between group and HBME-1 and CK-19 (H-score, proportion and intensity). The post-hoc comparison revealed that follicular adenoma was significantly more likely to have negative HBME-1 staining and a lower H-score when compared to follicular thyroid carcinoma and follicular variant of papillary thyroid carcinoma. The follicular variant of papillary thyroid carcinoma was significantly more likely to have an HBME-1 intensity of three and a higher H-score compared to follicular adenoma. Post-hoc comparison revealed that follicular adenoma was significantly more likely to have a negative CK-19 and a lower H-score when compared to follicular thyroid carcinoma and follicular variant of papillary thyroid carcinoma. Follicular variant of papillary thyroid carcinoma was significantly more likely to have a CK-19 intensity of three and a higher H-score compared to follicular thyroid carcinoma. HBME-1 had an overall specificity and sensitivity of 72% and 74% for distinguishing FA from FTC and FVPTC (benign from malignant). CK-19 had an overall specificity and sensitivity of 80.8% and 43.8% for distinguishing FA from FTC and FVPTC (benign from malignant). CK-19 had specificity of 87% and sensitivity of 72% for distinguishing FTC from FVPTC. Combining HBME-1 and CK-19 did not significantly increase the sensitivity and specificity of these markers. There was statistically no significant association between group and BRAF V600E and CD15 biomarkers. Conclusion: The study, within the small sample size power limitations, has shown that CK-19 may have a role in distinguishing follicular thyroid carcinoma from follicular variant of papillary thyroid carcinoma. In addition, HBME-1 and CK-19 may be used in differentiating benign follicular-patterned thyroid lesions from malignant follicular patterned thyroid lesions.